THE ROLE OF TEACHERS IN INCREASING STUDENT MOTIVATION OF STUDENTS IN SMAN 2 TOLITOLI DURING THE PANDEMIC COVID-19 - Saugadi Saugadi; Novia Ildra Permata Sari (Universitas Madako Tolitoli, 2020)
This study aims to determine the role of teachers in increasing student motivation at SMAN 2 TOLITOLI during the COVID-19 Pandemic. This study uses a qualitative approach with observation, interview and documentation procedures. This research was conducted at SMAN 2 TOLITOLI, which is located on Students street of 5 Tambun Village, Baolan District. The subjects of this study were one school principal, two educators at SMAN 2 TOLITOLI and two students at SMAN 2 TOLITOLI. The results showed that: the role of teachers at SMAN 2 TOLITOLI in increasing student learning motivation during the COVID-19 pandemic has played a role, can be seen through varied and interesting learning activities by utilizing learning media and selecting the right method so that student achievement is maintained and students will remain confident to pursue the goals you want to achieve. Through interesting learning activities and the awarding given based on rankings will spur student motivation to study hard. Not only in the process of learning the role of teachers during the COVID-19 pandemic, it leads to providing motivation to maintain a good environment to avoid the COVID-19 virus.Keywords :Student Learning Motivation, The Role of Teachers